Padci pri bolnikih po možganski kapi na oddelku za rehabilitacijo - Marolt, Melita (Rehabilitacija (Ljubljana), 2008)
Background: Stroke patients fall twice as often as the rest of the population and falls are among the most common complications after stroke. The aim of our retrospective study was to assess the characteristics of falls and of patients who fell during rehabilitation at the Department for rehabilitation of patients after stroke at the Institute for rehabilitation, Republic of Slovenia, in the year 2006, and consider possible measures for prevention of falls and their consequences. Methods: Data about stroke patients and falls were collected from medical documentation and official records on falls and possible injuries during rehabilitation. We compared the patients who fell once with the patients who fell more than once. Results: Nineteen percent of stroke patients admitted to our hospital experienced at least one fall during the hospitalisation; almost half of them fell more than once. There were no serious injuries. The patient's room or the lavatory was the most common site of fall; the falls occurred more frequently in the afternoon and during transfers, whereby hospital staff was usually not present. Mean admission FIM sub-scores for the use of lavatory and walking on stairs were significantly lower for the group that fell more than once, length of their rehabilitation was longer, and they were taking more drugs with sedative effect. Conclusions: Targeted falls prevention strategies, like more control over patients, education of patients and staff, and more careful prescription of drugs need to be systematically implemented as a part of each patient's stroke rehabilitation programme.
Keywords: padci; možganska kap; dejavniki tveganja; preprečevanje